2014
DOI: 10.1371/journal.pone.0115899
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids, Birdsong and Oxidative Status: Administration of Dietary Lutein Is Associated with an Increase in Song Rate and Circulating Antioxidants (Albumin and Cholesterol) and a Decrease in Oxidative Damage

Abstract: Despite the appealing hypothesis that carotenoid-based colouration signals oxidative status, evidence supporting the antioxidant function of these pigments is scarce. Recent studies have shown that lutein, the most common carotenoid used by birds, can enhance the expression of non-visual traits, such as birdsong. Nevertheless, the underlying physiological mechanisms remain unclear. In this study we hypothesized that male European starlings (Sturnus vulgaris) fed extra lutein increase their song rate as a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 84 publications
(129 reference statements)
7
43
0
Order By: Relevance
“…In the last decades several studies have investigated the role of the redox state in mediating the expression of visual secondary sexual traits (Alonso-Alvarez et al, 2007;McGraw, 2008;Svensson and Wong, 2011;Garratt and Brooks, 2012;Hill and Johnson, 2012;Simons et al, 2012), but until now only few of them focused on birdsong (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015Baldo et al, 2015;Costantini et al, 2015; Table 1). Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…In the last decades several studies have investigated the role of the redox state in mediating the expression of visual secondary sexual traits (Alonso-Alvarez et al, 2007;McGraw, 2008;Svensson and Wong, 2011;Garratt and Brooks, 2012;Hill and Johnson, 2012;Simons et al, 2012), but until now only few of them focused on birdsong (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015Baldo et al, 2015;Costantini et al, 2015; Table 1). Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
“…Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015. Lutein is a hydroxycarotenoid synthetized by autotrophic organisms as an essential photosynthetic pigment.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
See 3 more Smart Citations